2014
DOI: 10.5505/tjtes.2014.72698
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic bone fractures associated with intra-abdominal solid organ injury

Abstract: BACKGROUND:We analyzed the clinical progression of trauma patients with pelvic bone fractures so to determine the risk factors associated with sustaining concurrent abdominal solid organ injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our study showed that the mass bleeding due to the spleen laceration attributed to the death soon without any timely treatment, which means for the CCI injuries, the injury management for the control of bleeding is necessary to reduce the deaths. Kwon et al [ 31 ] suggested that traumatic pelvic fracture patient prognosis needs to be improved through early diagnosis and prompt delivery of aggressive treatments based on rapid identification of abdominal solid organ injuries. However, previous pelvis trauma studies about bleeding control mostly focused on the injuries to the liver rather than the spleen, whereby numerous animal models were developed using pigs [ 32 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the mass bleeding due to the spleen laceration attributed to the death soon without any timely treatment, which means for the CCI injuries, the injury management for the control of bleeding is necessary to reduce the deaths. Kwon et al [ 31 ] suggested that traumatic pelvic fracture patient prognosis needs to be improved through early diagnosis and prompt delivery of aggressive treatments based on rapid identification of abdominal solid organ injuries. However, previous pelvis trauma studies about bleeding control mostly focused on the injuries to the liver rather than the spleen, whereby numerous animal models were developed using pigs [ 32 39 ].…”
Section: Discussionmentioning
confidence: 99%